Dust mite-derived Der f 3 activates a pro-inflammatory program in airway epithelial cells via PAR-1 and PAR-2 - Li, Bizhou; Zou, Zehong; Meng, Fanmei; Raz, Eyal; Huang, Yuye; Tao, Ailin; Ai, Yuncan (Molecular immunology, 2019)
•Der f 3 disrupts the airway epithelial barrier and induces a proinflammatory response in airway epithelial cells (AECs).•Der f 3 activates signaling pathways including NF-kB, MAP kinases, and calcium signaling in AECs via its protease activity.•Der f 3 activates the above signaling cascades via protease-activated receptors 1 and 2. Protease activity of allergens has been suggested to be involved in the pathogenesis of allergic diseases. The major allergen Der f 3 from Dermatophagoides farinae harbors serine protease activity, but its immunopathogenesis remains unclear. This study aims to explore the effect of Der f 3 on the airway epithelial barrier and on the molecular pathways by which Der f 3 induces inflammation. RNA-seq was performed to identify differentially expressed genes in bronchial airway epithelial cells (AEC) between native Der f 3 and heat-inactivated (H) Der f 3, coupled with real-time PCR (RT-PCR) and ELISA for validation. Unlike other protease allergens such as that induce Th2-promoting alarmins (IL-25, IL-33, TSLP) in AECs, Der f 3 induced pro-inflammatory cytokines and chemokines including IL-6, IL-8 and GM-CSF, which are known to promote Th17 response. These pro-inflammatory mediators were induced by Der f 3 via the MAPK and NF-κB pathways as well as the store-operated calcium signaling. Gene silencing with small interfering RNA in A549 and BEAS-2B cells indicated that activation of AECs by Der f 3 was mainly dependent on protease-activated receptor 2 (PAR-2), while PAR-1 was also required for the full activation of AECs. Double knock-down of PAR-1 and PAR-2 largely impaired Der f 3-inducecd IL-8 production and subsequent signaling pathways. Our data suggest that Der f 3 induces pro-inflammatory mediators in human epithelial cell lines via the PARs-MAPK-NF-κB axis. Our results provide a molecular mechanism by which Der f 3 may trigger the Th17-skewed allergic response toward house dust mites.